2018
DOI: 10.1155/2018/5892306
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Naoxintong Capsule in the Treatment of Patients with Cerebral Infarction and Carotid Atherosclerosis: A Systematic Review and Meta‐Analysis of Randomized Trials

Abstract: Objective Naoxintong capsule (NXT) has been widely used to treat patients with cerebral infarction and carotid atherosclerosis. However, it is uncertain whether there is robust evidence on the effects of NXT for cerebral infarction and carotid atherosclerosis. A systematic review and meta-analysis of randomized trials were performed to assess the efficacy of NXT in the treatment of cerebral infarction and carotid atherosclerosis. Methods The Cochrane Library, EMBASE, the Medline database, the Wanfang database,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
13
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 18 publications
(14 citation statements)
references
References 20 publications
1
13
0
Order By: Relevance
“…NXT has been widely used in the clinical treatment of cerebral infarction and carotid atherosclerosis [37]. It has become increasingly popular to be used in combination with other prescription drugs.…”
Section: Discussionmentioning
confidence: 99%
“…NXT has been widely used in the clinical treatment of cerebral infarction and carotid atherosclerosis [37]. It has become increasingly popular to be used in combination with other prescription drugs.…”
Section: Discussionmentioning
confidence: 99%
“…Naoxintong (NXT) capsule is a traditional Chinese herb compound according to the theory of traditional Chinese medicine. It could activate the blood circulation, clear collaterals, improve endothelial function and plays a pivotal role in anti-atherosclerosis [12,13]. In recent years, more and more clinical studies indicated that NXT could reduce the plaque area and carotid intima-media thickness [14], and it could relieve the symptoms of hypertension as well.…”
Section: The Effects Of Naoxintong Capsule On the Vascular Endotheliamentioning
confidence: 99%
“…NXT also can reduce the NO level and the expression of inducible nitric oxide synthase (iNOS) in the vessel wall to treat atheromatous (Zhong et al 2013). In clinics, NXT can be used for carotid atherosclerosis and cerebral infarction (Liang et al 2018), partly abrogate the impaired protective effect of high-density lipoprotein (HDL) on endothelial function (Lv et al 2016), and improve adverse cardiovascular events, atherosclerosis, and the expression of inflammatory factors in patients with acute coronary syndrome undergoing PCI, when combined with Danhong injection (Lv et al 2015;Zhao et al 2018).…”
Section: Introductionmentioning
confidence: 99%